Treatment with Delta-9-tetrahydrocannabinol/cannabidiol in Multiple Sclerosis: Influence on the Autonomy Profile according to the International Classification of Functioning, Disability and Health - Silvia Ciotti; Mary Micheli; Antonella Cometa; Claudia De Carlo; Giancarlo Martini; Andrea Marona; Laura Filippetti; Diego Carducci; Silvano Baratta; Mauro Zampolini; Francesco Corea (European Journal of Case Reports in Internal Medicine, 2021)
Multiple sclerosis (MS) is the most common cause of non-traumatic neurological disability in young adults. It has effects at different levels: physical, emotional, psychological, cognitive and social, with a great variety of signs and symptoms. In particular, spasticity contributes to reducing the motor performance of patients with MS, causing pain, reduction in distance walked and limitations in social life. We present the case of a 39-year-old woman with MS. She was treated with delta-9-tetrahydrocannabinol/cannabidiol and the outcome was assessed with the International Classification of Functioning Disability and Health core set framework.